Effects of Food and Antacids on Pharmacokinetics and Pharmacodynamics of Lesinurad, a Selective Urate Reabsorption Inhibitor. Issue 5 (12th February 2019) - Shen, Zancong; Lee, Caroline A.; Valdez, Shakti; Yang, Xiaojuan; Wilson, David M.; Flanagan, Talia; Gillen, Michael
Abstract: Two clinical studies were performed in healthy volunteers to investigate food and antacid effects on lesinurad, a novel selective uric acid reabsorption inhibitor approved for treatment of hyperuricemia associated with gout in combination with xanthine oxidase inhibitors. Study 1 evaluated a high‐fat, high‐calorie meal or high doses of antacids (3000 mg calcium carbonate or 1600 mg magnesium hydroxide/1600 mg aluminum hydroxide) on the pharmacokinetics (PK) and pharmacodynamics (PD) of 400 mg oral lesinurad. Study 2 evaluated low doses of antacids (1250 mg calcium carbonate or 800 mg magnesium hydroxide/800 mg aluminum hydroxide) on the PK and PD of 400 mg lesinurad. Food did not alter the plasma AUC of lesinurad and only reduced its Cmax by 18%. In the fasted conditions, high‐dose calcium carbonate reduced the Cmax and AUC of lesinurad by 54% and 38%, respectively, whereas high‐dose magnesium hydroxide/aluminum hydroxide reduced Cmax and AUC by 36% and 31%, respectively. Food enhanced the maximum serum urate (sUA)‐lowering effect of lesinurad by approximately 20% despite reducing the Cmax of lesinurad. High‐dose calcium carbonate decreased the urate‐lowering effect approximately 20% in the first 6 hours, whereas high‐dose magnesium hydroxide/aluminum hydroxide reduced the effect by 26%. Low‐dose calcium carbonate or magnesium hydroxide/aluminum hydroxide in the presence of food did not significantly affect plasma lesinurad Cmax and AUC or the sUA lowering and renal handling of uric acid. In summary, study results suggest food did not meaningfully alter lesinurad PK and PD. High doses of antacids reduced lesinurad AUC up to 40% and reduced the lesinurad uric acid‐lowering effect.